2011
DOI: 10.1021/es201539s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Nanosilver Oxysulfidation

Abstract: Among the many new engineered nanomaterials, nanosilver is one of the highest priority cases for environmental risk assessment. Recent analysis of field samples from water treatment facilities suggests that silver is converted to silver sulfide, whose very low solubility may limit the bioavailability and adverse impact of silver in the environment. The present study demonstrates that silver nanoparticles react with dissolved sulfide species (HS−, S2−) under relevant but controlled laboratory conditions to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
238
4
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(261 citation statements)
references
References 30 publications
14
238
4
5
Order By: Relevance
“…NP size has also been found to affect the rate and extent of dissolution, since surface area increases with decreasing size, exposing more atoms per volume to the surrounding medium. For both CuO and coated Ag NPs, decreasing the size of the NPs increases the dissolution (both the rate and the equilibrium concentration), whereas the size of ZnO nanoparticles does not appear to significantly increase dissolution (Baek and An 2011;Franklin et al 2007;Levard et al 2012;Liu et al 2011;Ma et al 2012;Misra et al 2012;Mortimer et al 2010;Navarro et al 2008;Xia et al 2008).…”
Section: Dissolution In Watermentioning
confidence: 98%
“…NP size has also been found to affect the rate and extent of dissolution, since surface area increases with decreasing size, exposing more atoms per volume to the surrounding medium. For both CuO and coated Ag NPs, decreasing the size of the NPs increases the dissolution (both the rate and the equilibrium concentration), whereas the size of ZnO nanoparticles does not appear to significantly increase dissolution (Baek and An 2011;Franklin et al 2007;Levard et al 2012;Liu et al 2011;Ma et al 2012;Misra et al 2012;Mortimer et al 2010;Navarro et al 2008;Xia et al 2008).…”
Section: Dissolution In Watermentioning
confidence: 98%
“…Thus, sulfidation occurred much slower than had been observed in laboratory studies using Na 2 S as the source of sulfide. 31,32 The slower sulfidation of the AgNPs in the sediments compared to laboratory sulfidation may be a result of the relatively low AVS/Ag molar ratio (0.5−1 in the terrestrial soil and sediment) and the presence of other metals (e.g., Fe) that would compete for the sulfide. The slower sulfidation could also be due to a limited amount of oxidant (e.g., dissolved oxygen) that would be required to oxidize the AgNPs during the sulfidation process.…”
Section: +mentioning
confidence: 99%
“…Given the low levels of AVS in the sediment, sulfidation may be occurring as a two step process whereby the particles oxidize and dissolve to release free Ag + ion which is then transformed to Ag 2 S and the Ag-sulfhydryl phases observed. 32 Silver thiosulfate complexes may also form, but a model compound for this complex was not included in the EXAFS study. Fortin and Campbell (2001) 55 found that silver uptake in aquatic systems was greater in the presence of thiosulfate than based on the free Ag + water concentrations, and importantly, their studies suggest the presence of an inorganic anion transport system where a Ag−thiosulfate complex could give rise to increased uptake in higher organisms, including fish.…”
Section: +mentioning
confidence: 99%
“…36,53,59,60,[63][64][65][66][67][68] Henglein and coworkers, who pioneered work on the interactions between ligands and AgNPs, explained this observation by postulating that a "pre-complexation" or "pre-oxidation" occurred when nucleophiles adsorbed to the nanoparticle surface. [65][66][67] According to their hypothesis, the coordination of a nucleophile to a surface silver atom results in the partial oxidation of that atom.…”
Section: Effects Of Ligands and Surface Coating On Agnp Dissolutionmentioning
confidence: 99%